Analysis of the Relationship between Tangible and Reliability with Patient Satisfaction in Level III Hospital Pharmacy Installations in Southeast Sulawesi - Irliham, Irliham; Tasnim, Tasnim; Saafi, La Ode (Waluya The International Science of Health Journal, 2023)
Backgrounds: Hospital Pharmaceutical Services are an inseparable part of the Hospital health service system which is oriented towards patient service, providing quality and affordable Pharmaceutical Preparations, Medical Devices and Consumable Medical Materials for all levels of society, including clinical pharmacy services. The results of the survey conducted in June 2021, the average tangible value was (6.70%), while the reliability value was (46.83%). The aim of this research is to analyze the relationship between Tangible and Reliability and Patient Satisfaction in Level III Hospital Pharmacy Installations in Southeast Sulawesi. Methods: This research is a quantitative study with a cross sectional study design. The population in this study was 314 people. The sample size was 206 people. Data was processed using the SPSS program. Results: Test results using the chi-square test show significance figures for five variables. Tangible variables show a value of pvalue = 0.634 > α value = 0.05 indicating there is no relationship between the service quality variable (tangible) and patient satisfaction in hospital pharmacy installations, the Reliability variable shows a significance value of Asym.sig pearson chi-square 0.004 < α value = 0.05 indicates there is a relationship between the service quality variable (Reliability) and patient satisfaction in the hospital pharmacy installation. Conclusion: It is necessary to improve the quality of service in order to maintain a satisfactory level of service, where the Hospital should continue to maintain conditions such as Tangible and Reliability dimensions.